(untitled) (Research, Society and Development, 2020)
The aim of this paper consisted of the relation examination between exchange rate variations and the Brazilian’sexport prices of tobacco, relation defined as the pass-through of exchange rate, having as reference the period from January, 2000 to January, 2020. The data was collected from the sites of the Ministry of Development, Industry and Foreign Trade – MDIC, of the Institute for Applied Economics – IPEA and in the WORLD BANK. In this sense, we used instrumental of time series, especially the Vector Error Correction Model. The results found provided indications that the degree of pass-through of the exchange rate for the export prices of tobacco occurred in an incomplete way, representing that depreciations of the exchange rate do not translate themselves in significant gains of competitiveness, since that they do not reduce expressively the export prices.